2015
DOI: 10.1186/s12985-015-0392-3
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of inflammatory cytokines in Rift Valley fever patients are indicative of severe disease

Abstract: BackgroundRift Valley fever (RVF) is a mosquito-borne viral zoonosis affecting domestic and wild ruminants, camels and humans. Outbreaks of RVF are characterized by a sudden onset of abortions and high mortality amongst domestic ruminants. Humans develop disease ranging from a mild flu-like illness to more severe complications including hemorrhagic syndrome, ocular and neurological lesions and death. During the RVF outbreak in South Africa in 2010/11, a total of 278 human cases were laboratory confirmed, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 55 publications
2
47
0
Order By: Relevance
“…Serum samples from 26 patients from the 2000 outbreak of RVFV in Saudi Arabia showed increased WBC and decreased platelets in fatal cases relative to levels in survivors (6,41). Elevated CRE and urea levels were found in patient samples from lethal cases from the 2010 South African outbreak of RVFV (42). Granulocytosis has also been noted in NHPs exposed to aerosolized encephalitic alphaviruses, particularly in severe or fatal infections (43)(44)(45)(46), as well as in human Japanese encephalitis cases (47,48).…”
Section: Discussionmentioning
confidence: 98%
“…Serum samples from 26 patients from the 2000 outbreak of RVFV in Saudi Arabia showed increased WBC and decreased platelets in fatal cases relative to levels in survivors (6,41). Elevated CRE and urea levels were found in patient samples from lethal cases from the 2010 South African outbreak of RVFV (42). Granulocytosis has also been noted in NHPs exposed to aerosolized encephalitic alphaviruses, particularly in severe or fatal infections (43)(44)(45)(46), as well as in human Japanese encephalitis cases (47,48).…”
Section: Discussionmentioning
confidence: 98%
“…Individuals who were infected with HIV had an increased mortality rate (75%) after RVFV infection compared to that of individuals who were HIV negative (28%), and all HIV-infected persons presented with CNS symptoms (24). In another study, 3 of 4 patients who presented with and succumbed to encephalitis were also found to be HIV positive (25). The known effects of HIV on the number and function of CD4 T cells suggest that individuals with T cell dysfunction might be at increased risk of developing severe RVFV disease, including encephalitis.…”
Section: Discussionmentioning
confidence: 96%
“…12,13 These key findings suggested that T cells may be involved in modulating RVFV disease, and are further supported by the discovery that HIV- positive patients infected with RVFV had increased case fatality rates and increased occurrence of CNS manifestations of disease. 14,15 The role of antibodies in disease protection prior to or shortly following exposure to a pathogen is well-established in infectious disease. 28 The long-standing dogma holds that antibodies prevent viral disease, but T cells are needed to clear viral infection once the disease is manifest.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data obtained in the mouse model suggested that the T cellmediated immune response, not just the antibody response, could be important in protecting animals (and by extension, humans) from disease. 12,13 Additionally, two reports assessed HIV-positive patients who acquired RVFV infection; these patients exhibited increased frequency of central nervous system (CNS) symptoms and a significantly higher case fatality rate than HIV-negative patients, 14,15 suggesting the importance of CD4 T cells in preventing CNS manifestations and decreasing the severity of RVFV disease. Given these findings, it was of interest to quantitate and characterize T cell-mediated immune responses in humans.…”
Section: Introductionmentioning
confidence: 99%